Carpal Tunnel Cross-Sectional Area Affected by Soft Tissues Abutting the Carpal Bones - Gabra, Joseph N.; Li, Zong-Ming (Journal of Wrist Surgery, 2013)
The carpal tunnel accommodates free movement of its contents, and the tunnel's cross-sectional area is a useful morphological parameter for the evaluation of the space available for the carpal tunnel contents and of potential nerve compression in the tunnel. The osseous boundary of the carpal bones at the dorsal border of the carpal tunnel is commonly used to determine the tunnel area, but this boundary contains soft tissues such as numerous intercarpal ligaments and the flexor carpi radialis tendon. The aims of this study were to quantify the thickness of the soft tissues abutting the carpal bones and to investigate how this soft tissue influences the calculation of the carpal tunnel area. Magnetic resonance images were analyzed for eight cadaveric specimens. A medical balloon with a physiological pressure was inserted into an evacuated tunnel to identify the carpal tunnel boundary. The balloon-based (i.e., true carpal tunnel) and osseous-based carpal tunnel boundaries were extracted and divided into regions corresponding to the hamate, capitate, trapezoid, trapezium, and transverse carpal ligament (TCL). From the two boundaries, the overall and regional soft tissue thicknesses and areas were calculated. The soft tissue thickness was significantly greater for the trapezoid (3.1 ± 1.2 mm) and trapezium (3.4 ± 1.0 mm) regions than for the hamate (0.7 ± 0.3 mm) and capitate (1.2 ± 0.5 mm) regions. The carpal tunnel area using the osseous boundary (243.0 ± 40.4 mm2) was significantly larger than the balloon-based area (183.9 ± 29.7 mm2) with a ratio of 1.32. In other words, the carpal tunnel area can be estimated as 76% (= 1/1.32) of the osseous-based area. The abundance of soft tissue in the trapezoid and trapezium regions can be attributed mainly to the capitotrapezial ligament and the flexor carpi radialis tendon. Inclusion of such soft tissue leads to overestimations of the carpal tunnel area. Correct quantification of the carpal tunnel area aids in examining carpal tunnel stenosis as a potential risk factor for median nerve compression.
Keywords: area; carpal tunnel; carpal tunnel syndrome; stenosis